The famous five (five on a secret trail) - Blyton, Enid; Eileen Alice Soper (Great Britain Hodder and Stroughton, 1997)
The Famous Five are camping near an old ruined cottage, but is the cottage really abandoned? Anne hears strange noises at night, but the others don't believe her. Then they see ghostly lights...